2005
DOI: 10.1002/jms.736
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic morphine exposure on the synaptic plasma‐membrane subproteome of rats: a quantitative protein profiling study based on isotope‐coded affinity tags and liquid chromatography/mass spectrometry

Abstract: The effect of chronic morphine exposure on the synaptic plasma-membrane subproteome in rats was studied by the isotope-coded affinity tag (ICAT) method coupled with capillary reversed-phase liquid chromatography/electrospray ionization mass spectrometry and tandem mass spectrometry. ICAT-labeled tryptic peptides of synaptic membrane proteins were successfully identified using tandem mass spectrometry in conjunction with protein database searching. Several important synaptic plasma-membrane proteins displayed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
60
2
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 30 publications
4
60
2
1
Order By: Relevance
“…In addition, a number of studies also observed consistent and significant morphine-regulated alterations in the expression of chaperone proteins, specifically heat shock proteins including Hsp60 and Hsp70 (Prokai et al, 2005;Shui et al, 2007;Yang et al, 2007;Suder et al, 2009;Bu et al, 2012). Heat shock proteins such as HSP70 and HSP90 often serve as molecular chaperones, and both iTRAQ þ MS/MS analysis and western Blotting analyses have confirmed the presence of significantly elevated levels of HSP70 in the striatal PSD fraction following the induction of morphine dependence.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…In addition, a number of studies also observed consistent and significant morphine-regulated alterations in the expression of chaperone proteins, specifically heat shock proteins including Hsp60 and Hsp70 (Prokai et al, 2005;Shui et al, 2007;Yang et al, 2007;Suder et al, 2009;Bu et al, 2012). Heat shock proteins such as HSP70 and HSP90 often serve as molecular chaperones, and both iTRAQ þ MS/MS analysis and western Blotting analyses have confirmed the presence of significantly elevated levels of HSP70 in the striatal PSD fraction following the induction of morphine dependence.…”
Section: Discussionmentioning
confidence: 95%
“…Conversely, Li et al (2009) documented an increase in HSP72 in dorsal root ganglion cells subsequent to a 4-day escalating dependence paradigm, whereas the abundance of several heat shock proteins (HSC71, HSP1B, and HSP86) was upregulated in mouse hippocampal PSD fractions after short-term morphine treatment (Moron et al, 2007). Furthermore, a 7-day chronic morphine administration resulted in significantly elevated levels of HSP60 relative to saline controls (Prokai et al, 2005). Yet, HSP70 was found to be significantly downregulated in the primate NAc during the development of morphine dependence as well as during withdrawal while treated with either methadone or clonidine (Bu et al, 2012), and in the spinal cord of rats after repeated intrathecal morphine injections (Shui et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, the use of subcellular fractionation, which allows for the separation and generation of protein fractions selectively enriched in either pre-or postsynaptic proteins (25,27), in combination with proteomic analysis has revealed that an acute escalating dose of morphine administration produces significant alterations in the postsynaptic density (PSD) 1 associated protein network in the hippocampus. This includes significant redistribution of endocytic proteins such as clathrin (20,22) and glutamatergic ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors (12,13). Proteomic analysis coupled with tandem mass spectrometry (MS/MS) followed by the computational analysis that placed the proteomics results within known protein-protein interaction (PPI) networks also revealed a novel function for heat shock proteins and their co-chaperones in the presynaptic active zone of the morphine tolerant striatum.…”
mentioning
confidence: 99%